Поверхні зі зниженою роботою виходу: проблеми створення та теоретичного опису. Огляд - Strikha, M.V.; Goriachko, A.M. (Publishing house "Academperiodika", 2023)
Experimental studies devoted to the creation of the modern photocathodes or efficient field emission cathodes with lowered work function or low/negative electron affinity are reviewed. We present theoretical models, where the electron affinity lowering is associated with the influence of electrically charged layers at the semiconductor/insulator interface. Modern experimental techniques of measuring the work function or the electron affinity and technologies aimed at fabricating the surfaces with low work function/electron affinity are described. In the framework of a simple theoretical model developed by the authors, it has been demonstrated that the presence of a dipole layer (e.g., composed of negatively charged oxygen ions and positively charged rare earth ions) at the semiconductor surface can lower the electron affinity by up to 3 eV provided equal concentrations of oppositely charged adsorbate ions. It is also shown that if the surface concentration of negatively charged oxygen ions is higher than the surface concentration of positively charged metal ions, the lowering of the electron affinity becomes smaller due to the upward band bending in the space charge region in the semiconductor; otherwise, the lowering of the electron affinity becomes larger due to the downward band bending. This effect allows technological proposals to be formulated for obtaining surfaces with minimum work function values in modern field-emission-based electronic devices. In the framework of the proposed model, the work function was evaluated for the OH-functionalized MXene. The corresponding value for the unfunctionalized MXene equals about 4.5 eV, being practically independent of the number of Ti and C layers (from 1 to 9 layers). The OH-functionalization lowers it down to about 1.6 eV, and this value is also practically independent of the number of atomic layers in MXene. Experimental approaches to obtain cathodes with low work function/low electron affinity are described. They are aimed at creating a spatial separation of electric charges in the near-surface cathode region perpendicularly to the surface plane. The corresponding spatial distributions of positive and negative charges are characterized by their localization either in two different atomic planes or in one plane and an extended space region (the latter variant is typical of semiconductor substrates). The technologies for producing such surfaces are based on various methods of adsorbate deposition onto the metal or semiconductor substrate: physical vapor deposition, chemical vapor deposition, liquid phase deposition, diffusion from the substrate bulk, and so forth. Particular attention is paid to the experimental works dealing with the adsorbtion of rare earth metals (Ce, Gd, Eu) and the coadsorbtion of oxygen onto the Si, Ge, and Mo surfaces (in a nano-structured state as well), which results in the dipole layer formation and the work function reduction.